2012
DOI: 10.1007/s11042-012-1101-5
|View full text |Cite
|
Sign up to set email alerts
|

Understanding fish behavior during typhoon events in real-life underwater environments

Abstract: The study of fish populations in their own natural environment is a task that has usually been tackled in invasive ways which inevitably influenced the behavior of the fish under observation. Recent projects involving the installation of permanent underwater cameras (e.g. the Fish4Knowledge (F4K) project, for the observation of Taiwan's coral reefs) allow to gather huge quantities of video data, without interfering with the observed environment, but at the same time require the development of automatic process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 58 publications
0
30
0
Order By: Relevance
“…These results show that the system performance is comparable to those of by state-of-the-art approaches performing on much simpler events [1,9].…”
Section: Event Detectionmentioning
confidence: 62%
See 2 more Smart Citations
“…These results show that the system performance is comparable to those of by state-of-the-art approaches performing on much simpler events [1,9].…”
Section: Event Detectionmentioning
confidence: 62%
“…To tackle these problems, we developed an algorithm specifically designed for tracking fish in unconstrained underwater environments [6,9]. It is based on a covariance representation of fish features [52].…”
Section: Fish Tracking For Trajectory Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…[49,19], the most important step in the automated visual analysis has been done in the EU-funded Fish4Knowledge (F4K) 17 project, where computer vision methods were developed to extract information about fish density and richness from videos taken by underwater cameras installed at coral reefs in Taiwan [62,63,6,61]. Since the F4K project, many researchers have directed their attention towards underwater video analysis [53,55], including some recent initiatives by the National Oceanographic and Atmospheric Administration (NOAA) [57] and the fish identification task at LifeCLEF 2014 and 2015 [12,13,60].…”
Section: Coral Reef Species Identification In Underwater Videosmentioning
confidence: 99%
“…They trained the system on lion faces and showed that the results can be used to classify basic locomotive actions. Spampinato et al [19,20] proposed a system for fish detection, tracking, and species classification in natural underwater environment. They first detect fishes using a combination of a Gaussian mixture model and moving average algorithms.…”
Section: Visual Detectionmentioning
confidence: 99%